Pengaruh Asimetri Informasi, Pengendalian Intern Dan Budaya Organisasi Terhadap Kecenderungan Kecurangan (Fraud) Lpd Se-Kecamatan Banjarangkan - I Made Wahyu Adi Valentina; Kadek Dewi Padnyawati (Hita Akuntansi dan Keuangan, 2023)
This study is a case on LPD employees in Banjarangkan District. It aims to determine the effect of fraud — also known as information asymmetry — on organizational culture, internal control and external control. The study's population is all of the LPDs in Banjarangkan District; this includes 30 active LPDs with 2 inactive LPDs. To collect data for analysis, the researchers used a random selection method and tested the results with multiple linear regression analysis. The results indicated that there was a positive and significant influence between fraud and information asymmetry among LPD employees in Banjarangkan District. The results of this study can be used to create regulations and policies for preventing fraud in LPDs in Banjarangkan District. Additionally, this study shows a negative effect from internal control and a negative effect from organizational culture on fraud tendencies in LPDs in Banjarangkan District.